2019
DOI: 10.1101/715003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Platelet disturbances correlate with endothelial cell activation in uncomplicated Plasmodium vivax malaria

Abstract: 23Introduction. Platelets drive endothelial cell activation in many diseases. 24 However, if this occurs in Plasmodium vivax malaria is unclear. As platelets have 25 been reported to be activated and to play a role in inflammatory response during 26 malaria, we hypothesized that this would correlate with endothelial alterations 27 during acute illness. 28Methods. We performed platelet flow cytometry of PAC-1 and P-selectin. We 29 measured Platelet markers (CXCL4, CD40L, P-selectin, Thrombopoietin, IL-11) an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(33 reference statements)
2
2
0
Order By: Relevance
“…Patients with severe thrombocytopenia also show more severe leukopenia, lymphopenia and mega platelets (higher MPV). In addition, Our data support previous studies suggesting a role for endothelial cell (EC) activation and damage in increased leukocyte adhesion, intravascular platelet agglutination with increased platelet clearance from the circulation and skewing of haematopoiesis toward the myeloid lineage (likely at the expense of lymphopoiesis) in the BM [28][29][30][33][34][35]41,42,45 . P. vivax elicits a stronger inflammatory response and more pronounced endothelial activation when compared with other Plasmodium infections with similar or higher peripheral parasitaemia 23 , however the role of EC activation in P. vivax pathogenesis is not yet understood.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Patients with severe thrombocytopenia also show more severe leukopenia, lymphopenia and mega platelets (higher MPV). In addition, Our data support previous studies suggesting a role for endothelial cell (EC) activation and damage in increased leukocyte adhesion, intravascular platelet agglutination with increased platelet clearance from the circulation and skewing of haematopoiesis toward the myeloid lineage (likely at the expense of lymphopoiesis) in the BM [28][29][30][33][34][35]41,42,45 . P. vivax elicits a stronger inflammatory response and more pronounced endothelial activation when compared with other Plasmodium infections with similar or higher peripheral parasitaemia 23 , however the role of EC activation in P. vivax pathogenesis is not yet understood.…”
Section: Discussionsupporting
confidence: 89%
“…Patient clustering indicated that Vivax high patients have increased levels of EC markers in the plasma compared to Vivax low patients (Figure 2C). Previous studies indicate that EC activation and damage might contribute to thrombocytopenia and inducing hematopoiesis, resulting in HSC differentiation directed towards myelopoiesis 24,28,29,[33][34][35][41][42][43] . In our cohort, circulating levels of EC adhesion molecules (ICAM-1, VCAM-1, E-selectin and P-selectin) and other EC activation markers and procoagulant molecules (Ang-2, VWF-A2, CD40L and PAI-1) were significantly increased in the plasma of Vivax high patients compared to Vivax low patients and healthy controls (Figures 5A, Figure 5-figure supplement 1A, B).…”
Section: Vivax Low Patientsmentioning
confidence: 99%
“…Platelet and erythrocyte sequestration are frequent in the severe forms of malaria, and thrombocytopenia is present [30]. Thrombocytopenia in this study might also be associated with endothelial damage and isolated platelet consumption [31]. Our results showed significant increases in platelet count in mice treated with 250 and 500 mg/kg of GIE and CQ when compared to healthy control, suggesting their role as an acute phase reactant to infection.…”
Section: Discussionsupporting
confidence: 55%
“…PAF recruits and activates leukocytes, increases cytokine and chemokine secretion, and modulates vascular permeability. [117,118]…”
Section: Interaction Between Vascular Endothelium and Plateletsmentioning
confidence: 99%